2022
DOI: 10.1038/s41598-022-23155-3
|View full text |Cite
|
Sign up to set email alerts
|

Extreme temperature increases the risk of stillbirth in the third trimester of pregnancy

Abstract: Epidemiological studies have reported the association between extreme temperatures and adverse reproductive effects. However, the susceptible period of exposure during pregnancy remains unclear. This study aimed to assess the impact of extreme temperature on the stillbirth rate. We performed a time-series analysis to explore the associations between temperature and stillbirth with a distributed lag nonlinear model. A total of 22,769 stillbirths in Taiwan between 2009 and 2018 were enrolled. The mean stillbirth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As deaths are usually considered rare events, HR and relative risk (RR) were assumed to be a reasonable approximation of each other in this study with caution 53 – 55 . Then, regression coefficients corresponding to ENSO measures were used to calculate the AF of deaths and the number of deaths attributable to extreme levels of ENSO, using commonly described approaches as follows 56 : where RR is approximated by the HR of La Niña, weak El Niño, or moderate El Niño conditions considering the neutral condition as the reference. We calculated the number of deaths attributable to exposure to La Niña, weak El Niño, or moderate El Niño by multiplying the AF with the number of deaths under these conditions.…”
Section: Methodsmentioning
confidence: 99%
“…As deaths are usually considered rare events, HR and relative risk (RR) were assumed to be a reasonable approximation of each other in this study with caution 53 – 55 . Then, regression coefficients corresponding to ENSO measures were used to calculate the AF of deaths and the number of deaths attributable to extreme levels of ENSO, using commonly described approaches as follows 56 : where RR is approximated by the HR of La Niña, weak El Niño, or moderate El Niño conditions considering the neutral condition as the reference. We calculated the number of deaths attributable to exposure to La Niña, weak El Niño, or moderate El Niño by multiplying the AF with the number of deaths under these conditions.…”
Section: Methodsmentioning
confidence: 99%
“…6,28 Comparing our effects of ambient temperature on stillbirth mortality with other estimates is challenging as studies are heterogeneous in terms of exposure metric, unit change, and time period of effect. Generally, evidence is stronger for an acute effect of heat (i.e., in the last weeks or trimester of pregnancy) [29][30][31][32][33][34] than for a delayed effect occurring in the 1st or 2nd trimester. 16,34 Few studies have evaluated associations between temperature in the week before birth and stillbirths as we did.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, evidence is stronger for an acute effect of heat (i.e., in the last weeks or trimester of pregnancy) [29][30][31][32][33][34] than for a delayed effect occurring in the 1st or 2nd trimester. 16,34 Few studies have evaluated associations between temperature in the week before birth and stillbirths as we did. A recent systematic review and meta-analysis (Chersich et al, 6 ) included two studies from high income countries using the same analysis method (lag 0-6).…”
Section: Discussionmentioning
confidence: 99%
“…In Western Australia, risk of stillbirth was found to increase by 19% (95% CI 17%–21%) when women were exposed to moderate heat stress (99th centile UTCI, 31.7°C) versus no thermal stress (50th centile UTCI, 13.9°C) throughout the last week of pregnancy, and by 41% (95% CI 38%–44%) when exposed to moderate heat stress throughout the last 2 weeks of pregnancy 25 . In Taiwan, Yang et al 26 estimated that 2.64% of all stillbirths are attributable to high ambient temperature exposures (>29°C). They found that women are most susceptible to adverse heat effects in the third trimester of pregnancy, with a 2.4‐fold (95% CI 1.19–4.8) increased risk of stillbirth when exposed to the 99th centile of monthly mean temperature (30.1°C) versus the optimal temperature (21°C) 0–3 months before delivery.…”
Section: Environmental Temperature and Stillbirth: Epidemiological Ev...mentioning
confidence: 99%